Insights into Hydrocarbon Assimilation by Eurotialean and Hypocrealean Fungi : Roles for CYP52 and CYP53 Clans of Cytochrome P450 Genes - Huarte Bonnet, Carla (2017)
Several filamentous fungi are able to concomitantly assimilate both aliphatic and polycyclic aromatic hydrocarbons that are the biogenic by-products of some industrial processes. Cytochrome P450 monooxygenases catalyze the first oxidation reaction for both types of substrate. Among the cytochrome P450 (CYP) genes, the family CYP52 is implicated in the first hydroxylation step in alkane-assimilation processes, while genes belonging to the family CYP53 have been linked with oxidation of aromatic hydrocarbons. Here, we perform a comparative analysis of CYP genes belonging to clans CYP52 and CYP53 in Aspergillus niger, Beauveria bassiana, Metarhizium robertsii (formerly M. anisopliae var. anisopliae), and Penicillium chrysogenum. These species were able to assimilate n-hexadecane, n-octacosane, and phenanthrene, exhibiting a species-dependent modification in pH of the nutrient medium during this process. Modeling of the molecular docking of the hydrocarbons to the cytochrome P450 active site revealed that both phenanthrene and n-octacosane are energetically favored as substrates for the enzymes codified by genes belonging to both CYP52 and CYP53 clans, and thus appear to be involved in this oxidation step. Analyses of gene expression revealed that CYP53 members were significantly induced by phenanthrene in all species studied, but only CYP52X1 and CYP53A11 from B. bassiana were highly induced with n-alkanes. These findings suggest that the set of P450 enzymes involved in hydrocarbon assimilation by fungi is dependent on phylogeny and reveal distinct substrate and expression specificities.